Conductive polymer solution for capacitors, solid electrolytic capacitor and manufacturing method
Patent Information
- Application Number
- JP2023138287
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-12
AI Technical Summary
【0024】 固体電解コンデンサの静電容量を向上させることができる。
Smart Images

Figure 2025032805000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive polymer solution for a capacitor for forming a solid electrolyte layer in a solid electrolytic capacitor, a solid electrolytic capacitor in which a solid electrolyte layer is interposed between an anode foil and a cathode foil, and a method for manufacturing a solid electrolytic capacitor using the conductive polymer solution for a capacitor. [Background technology]
[0002] An electrolytic capacitor has anode and cathode foils made of valve metals such as tantalum or aluminum. The anode foil is enlarged by forming the valve metal into a sintered or etched foil, and the enlarged surface has a dielectric oxide film formed by anodizing or other treatment. An electrolyte is interposed between the anode and cathode foils.
[0003] Electrolytic capacitors have the advantage that they can easily obtain a large capacitance compared to other types of capacitors because the specific surface area can be increased by expanding the surface area of the anode foil. Electrolytic capacitors contain electrolyte in the form of an electrolytic solution. The contact area of the electrolyte with the dielectric oxide film of the anode foil increases. This makes it easier to further increase the capacitance of electrolytic capacitors.
[0004] In recent years, solid electrolytic capacitors, which use a solid electrolyte with higher conductivity than the electrolyte, have also been attracting attention. Solid electrolytic capacitors use a solid electrolyte with higher conductivity than the electrolyte, and can achieve low equivalent series resistance (ESR). Manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes are known as solid electrolytes.
[0005] In addition, conductive polymers derived from monomers with π-conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), which has excellent adhesion to dielectric oxide films, are rapidly becoming popular as solid electrolytes. Conductive polymers use polystyrene sulfonate (PSS) as a dopant to achieve high conductivity. Therefore, solid electrolytic capacitors have the advantage of low equivalent series resistance (ESR).
[0006] A solid electrolyte containing a conductive polymer is formed by applying or impregnating a conductive polymer dispersion between an anode foil and a cathode foil, and drying the dispersion medium. The conductive polymer dispersion is a dispersion of a conductive polymer, and for example, water is used as the dispersion medium to disperse the conductive polymer in water. The conductive polymer is produced by mixing a monomer, which becomes a monomer unit of the conductive polymer, a dopant, and an oxidizing agent, and subjecting the mixture to chemical oxidative polymerization.
[0007] The conductive polymer dispersion containing PEDOT doped with PSS is adjusted to pH 3 to 13 with an alkaline compound (see, for example, Patent Document 1). If the pH is less than 3, the acidity is too strong and corrosion of the dielectric oxide film and the cathode foil cannot be prevented, whereas if the pH exceeds 13, the conductive polymer is de-doped, resulting in insufficient conductivity of the solid electrolyte layer.
[0008] However, it continues to be pointed out that even if the pH of the conductive polymer dispersion is adjusted to 3 to 13, the ESR and capacitance are not sufficient in terms of performance (see, for example, Patent Document 2). Therefore, a proposal has been presented to adjust the content of the alkaline compound based on the neutralization equivalent of the conductive polymer. However, if the pH of the conductive polymer dispersion is shifted to the alkaline side, dedoping of PSS is likely to occur, so in recent years, it has been considered preferable to have a range from weak acidity to neutrality with an upper limit of pH 8 at most (see, for example, Patent Document 3).
[0009] The purpose of the alkaline compound is to adjust the pH, so theoretically any alkaline compound is conceivable for this purpose only. However, in practice, ammonia is often used as the alkaline compound added to the conductive polymer dispersion. Ammonia is weakly basic and it is difficult to undo PSS from PEDOT, but if the basicity is stronger than ammonia, the undoping of PSS increases, and the ESR increases even at a pH of 8 or less (see, for example, Patent Document 3).
[0010] In addition, ammonia is volatile and can be easily removed by a process involving heating, making it difficult to de-dop PSS. Furthermore, ammonia has a small molecular size, and even if it forms an ion pair with PSS, it can suppress the reduction in effective conjugation length caused by the twisting of the PEDOT main chain, making it difficult to de-dop PSS.
[0011] Regarding the suppression of ESR, inorganic alkali compounds alone and organic alkali compounds alone tend to improve the withstand voltage characteristics, but it has been shown that the increase in ESR in a high-temperature environment is not sufficiently suppressed, and liquid compositions containing two or more types of alkali compounds have also been proposed (see, for example, Patent Document 3). The liquid composition is a conductive polymer dispersion. The two or more types of alkali compounds are essentially a combination of ammonia and amine.
[0012] That is, the example shows that the ESR is better than when ammonia is added alone to the liquid composition. However, although the pH range of 8 may be suggested as a range from weak acidity to neutrality, it is realistic to optimize the pH range to 5 or less (see, for example, Patent Document 3). [Prior art documents] [Patent documents]
[0013] [Patent Document 1] JP 2006-287182 A [Patent Document 2] JP 2014-67949 A [Patent Document 3] International Publication No. 2018 / 123255 Summary of the Invention [Problem to be solved by the invention]
[0014] Thus, there has been technological progress in terms of suppressing the ESR of solid electrolytic capacitors. However, since it was pointed out that conductive polymer dispersions with a pH of 3 to 13 are not sufficient in terms of capacitance performance, it cannot be said that sufficient research has been conducted on measures to fully utilize the capacitance of solid electrolytic capacitors from the perspective of the composition of conductive polymer dispersions. Moreover, in recent years, electronic and electrical devices have become significantly smaller and more powerful. Therefore, there is a demand for further improvement in capacitance of solid electrolytic capacitors as well.
[0015] The present invention has been proposed to solve the above-mentioned problems, and an object of the present invention is to provide a conductive polymer solution for a capacitor for increasing the capacitance of a solid electrolytic capacitor, a solid electrolytic capacitor with increased capacitance, and a manufacturing method thereof. [Means for solving the problem]
[0016] In order to solve the above problems, the conductive polymer solution for a capacitor according to the present embodiment contains a polymer of 3,4-ethylenedioxythiophene in which a methylenephosphonic acid group is introduced into the ethylenedioxy skeleton, an amine, and ammonia.
[0017] The amine may be a secondary amine or a tertiary amine.
[0018] The pH may be less than 10.
[0019] The pH may be 9 or greater.
[0020] The pH may be around 9.
[0021] The amine may be contained in an amount, in terms of mass ratio, equal to or greater than the ammonia content.
[0022] In order to solve the above problems, the solid electrolytic capacitor of the present embodiment includes an anode foil having a dielectric oxide film formed thereon, and a solid electrolyte layer containing a conductive polymer, the conductive polymer being a polymer of 3,4-ethylenedioxythiophene having a methylenephosphonic acid group introduced into an ethylenedioxy skeleton, and the solid electrolyte layer containing an amine and ammonia.
[0023] In order to solve the above problems, the method for manufacturing a solid electrolytic capacitor of the present embodiment is a method for manufacturing a solid electrolytic capacitor having an anode foil on which a dielectric oxide film is formed, and includes a solid electrolyte layer formation step of adhering such a conductive polymer solution for a capacitor to the anode foil and drying it. Effect of the Invention
[0024] The capacitance of the solid electrolytic capacitor can be improved. [Brief description of the drawings]
[0025] [Figure 1] The Cap values for Examples 1 to 6, Comparative Example 1, and Reference Examples 1 and 2 are shown when the measurement frequency is 120 Hz. [Diagram 2] The Cap values for Examples 1 to 6, Comparative Example 1, and Reference Examples 1 and 2 are shown at a measurement frequency of 10 kHz. [Diagram 3] The ESR values shown are for Examples 1 to 6, Comparative Example 1, and Reference Examples 1 and 2, measured at a frequency of 100 kHz. [Figure 4] 1 shows the Cap at a measurement frequency of 120 Hz for Examples 7 to 14. [Diagram 5] The measurement frequency of Examples 7 to 14 is 10 kHz. [Figure 6] 1 shows the ESR at a measurement frequency of 100 kHz for Examples 7 to 14. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, a conductive polymer solution for a capacitor, a solid electrolytic capacitor, and a manufacturing method thereof according to embodiments of the present invention will be described. Note that the present invention is not limited to the embodiments described below.
[0027] (Conductive polymer solution for capacitors) A conductive polymer solution for capacitors (hereinafter referred to as polymer solution) is a solution for forming a solid electrolyte layer in a solid electrolytic capacitor. A solid electrolytic capacitor is a passive element that stores and discharges electric charge by electrostatic capacitance, and an anode foil and a cathode foil on which a dielectric oxide film is formed are opposed to each other via a separator, and a solid electrolyte layer is interposed between the anode foil and the cathode foil. The solid electrolyte layer contains a conductive polymer. The conductive polymer of the solid electrolyte layer is dissolved in the polymer solution. The solid electrolyte layer is formed by applying the polymer solution to the dielectric oxide film of the anode foil and drying it.
[0028] The conductive polymer is a polymer of 3,4-ethylenedioxythiophene in which a methylenephosphonic acid group has been introduced into the ethylenedioxy skeleton. As an example of this conductive polymer, as represented by the following chemical formula (A), a polymer of 3,4-ethylenedioxythiophene in which a methylenephosphonic acid group has been introduced into the 2-position of the ethylenedioxy skeleton can be given. Alternatively, as an example of this conductive polymer, a polymer of 3,4-ethylenedioxythiophene in which a methylenephosphonic acid group has been introduced into the 1-position of the ethylenedioxy skeleton can be given.
[0029] [ka]
[0030] The conductive polymer may be a homopolymer formed by polymerizing only the monomer of 3,4-ethylenedioxythiophene having a methylenephosphonic acid group introduced into the ethylenedioxy skeleton, or a copolymer containing this monomer unit and 3,4-ethylenedioxythiophene or a derivative of 3,4-ethylenedioxythiophene. Hereinafter, the polymer of 3,4-ethylenedioxythiophene having a methylenephosphonic acid group introduced into the ethylenedioxy skeleton is referred to as phosphonic acid group-introduced PEDOT.
[0031] In phosphonic acid group-introduced PEDOT, the methylene phosphonic acid group in the side chain acts as a hydrogen ion-donating dopant. Therefore, phosphonic acid group-introduced PEDOT exhibits conductivity as a self-doped conductive polymer. Furthermore, as the dissociation of the methylene phosphonic acid group progresses, the solubility in solvents improves, and phosphonic acid group-introduced PEDOT becomes soluble in water.
[0032] Amine and ammonia are added to the polymer solution in which the phosphonic acid group-introduced PEDOT is dissolved. The pH of the polymer solution is adjusted to more than 8, from about 9 to less than 10, by adding the amine and ammonia. As the amine, alkylamines and alkanolamines are preferred, and secondary amines or tertiary amines are particularly preferred because of their strong basicity. The amine may be a derivative having a substituent. Around pH 9 is the vicinity of pH 9, which is pH 8.5 to 9.5.
[0033] Examples of secondary amines include dimethylamine, diethylamine, dipropylamine, methylethylamine, diethanolamine, etc. Examples of tertiary amines include trimethylamine, triethylamine, ethyldimethylamine, dimethyloctylamine, diethyloctylamine, dimethylaminoethanol, dimethylaminoethoxyethanol, etc.
[0034] In such a polymer solution, the phosphonic acid group-introduced PEDOT is a self-doped conductive polymer, and is therefore more difficult to undo than a conductive polymer made of poly(3,4-ethylenedioxythiophene) (PEDOT) doped with polystyrene sulfonic acid (PSS) (hereinafter referred to as PEDOT:PSS). Therefore, the pH of the polymer solution can be increased to the alkaline side. When the polymer solution with an alkaline pH is dried, the phosphonic acid group-introduced PEDOT solubilized in the solution precipitates.
[0035] Here, the solid electrolyte layer creates a conductive path between the dielectric oxide film and the cathode foil, and the solid electrolyte layer becomes the true cathode. If the phosphonic acid group-introduced PEDOT cannot be sufficiently filled in the surface expansion layer of the anode foil, the opposing area of the anode and cathode will be small. If the opposing area is small, the capacitance of the solid electrolytic capacitor will decrease. Moreover, in recent years, the surface expansion layer of the anode foil has become denser and the voids have become smaller in order to expand the surface area in order to improve capacitance.
[0036] However, since the phosphonic acid group-introduced PEDOT is solubilized in the solution by amine and ammonia, it is fully filled into the surface-expanding layer of the anode foil, improving the capacitance of the solid electrolytic capacitor. Moreover, the methylene phosphonic acid group of the phosphonic acid group-introduced PEDOT has high adsorption to the anode foil, improving the adhesion between the solid electrolyte layer and the dielectric oxide film, and reducing the dissociation area between the dielectric oxide film and the solid electrolyte layer.
[0037] However, if the pH is too high, even PEDOT with phosphonic acid groups will undergo dedoping, and the ESR of the solid electrolytic capacitor will increase. Ammonia, which is used to adjust the pH of PEDOT:PSS, is weakly basic and has a small molecular size, so when the polymer solution is weakly alkaline at around pH 9, not only will it cause the polymer solution to gel, but the ESR of the solid electrolytic capacitor will become extremely high. In this regard, amines, which are strongly basic and have a bulky molecular structure, promote the dissociation of phosphonic acid groups and therefore suppress the aggregation of PEDOT with phosphonic acid groups, even when the polymer solution is in the relatively weakly alkaline range of pH 9 to 10.
[0038] In other words, if the hydrogen atoms of the phosphonic acid groups of phosphonic acid-introduced PEDOT form hydrogen bonds, the phosphonic acid-introduced PEDOT will aggregate. However, if these hydrogen atoms are replaced with amines, hydrogen bonds do not occur and the aggregation of the phosphonic acid-introduced PEDOT is suppressed.
[0039] When an amine is added to the polymer solution in addition to ammonia, the polymer solution does not gel even if the polymer solution is weakly alkaline at around pH 9 due to the influence of the amine or the interaction between the ammonia and the amine. Therefore, when the phosphonated PEDOT, ammonia, and an amine are added to the polymer solution, the phosphonated PEDOT can be made into small particles and solubilized without agglomerating the phosphonated PEDOT in the polymer solution or causing dedoping. Furthermore, a solid electrolytic capacitor having a solid electrolyte layer containing the solubilized phosphonated PEDOT has improved capacitance.
[0040] When the polymer solution is adjusted to pH 10 or higher using ammonia alone, the aggregation of phosphonate-introduced PEDOT is finally suppressed. The phosphonate-introduced PEDOT is then reduced in particle size, but the improvement in the capacitance of the solid electrolytic capacitor is still slight. On the other hand, when the pH of the polymer solution is increased to 10 or higher, even the phosphonate-introduced PEDOT is de-doped, and the ESR of the solid electrolytic capacitor increases.
[0041] However, even when ammonia and amine are added, the ESR begins to rise when the pH exceeds 10. The amine has a bulky molecular structure. When many amines are close to the phosphonate group-introduced PEDOT, the dedoping proceeds slowly, and the ESR begins to rise. The reason why the dedoping proceeds slowly is due to the shortening of the effective conjugation length caused by the twisting of the main chain of the phosphonate group-introduced PEDOT. Therefore, it is preferable to set the pH of the polymer solution to less than 10. The combination of PEDOT:PSS and amine is not preferable because the amine has a strong basicity and a bulky molecular structure, and therefore dedoping proceeds immediately when the pH exceeds the neutralization point of PSS.
[0042] The mixing ratio of ammonia and amine is not particularly limited. Preferably, the amine is contained in the polymer solution in an amount equal to or greater than the amount of ammonia in terms of mass ratio. When the amount of amine is equal to or greater than the amount of ammonia in terms of mass ratio, the ESR and capacitance of the solid electrolytic capacitor are both in a particularly good range.
[0043] The solvent of the polymer solution is not particularly limited as long as it dissolves the phosphonic acid group-introduced PEDOT. The solvent of the polymer solution is typically water, but may also be an organic solvent or a mixture of an organic solvent and water. Examples of the organic solvent include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, and nitrile compounds.
[0044] Examples of polar solvents include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. Examples of alcohols include methanol, ethanol, propanol, and butanol. Examples of esters include ethyl acetate, propyl acetate, and butyl acetate. Examples of hydrocarbons include hexane, heptane, benzene, toluene, and xylene. Examples of carbonate compounds include ethylene carbonate and propylene carbonate. Examples of ether compounds include dioxane and diethyl ether. Examples of chain ethers include ethylene glycol dialkyl ether, propylene glycol dialkyl ether, polyethylene glycol dialkyl ether, and polypropylene glycol dialkyl ether. Examples of heterocyclic compounds include 3-methyl-2-oxazolidinone. Examples of nitrile compounds include acetonitrile, glutarodinitrile, methoxyacetonitrile, propionitrile, and benzonitrile.
[0045] The polymer solution may further contain additives such as polyhydric alcohols. Examples of polyhydric alcohols include polyethylene glycol, 1-hexanol, ethylene glycol, diethylene glycol, triethylene glycol, glycerin, or a combination of two or more of these. Since polyhydric alcohols have a high boiling point, they remain in the solid electrolyte layer even after the polymer solution is dried. Furthermore, the polymer solution may contain conventional additives such as organic binders, surfactants, dispersants, antifoaming agents, coupling agents, antioxidants, and ultraviolet absorbers.
[0046] The method for producing such a polymer solution is not particularly limited, but it can be obtained, for example, by the following production method.
[0047] First, the method for producing phosphonic acid group-introduced PEDOT is as follows. That is, 3,4-ethylenedioxythiophene in which a methylene group having a halogen substituent has been introduced into the ethylenedioxy skeleton is heated in the presence of an acid catalyst such as sulfuric acid, paratoluenesulfonic acid, or methanesulfonic acid. The Michaelis-Arbuzov transfer reaction is caused between 3,4-ethylenedioxythiophene in which a methylene group having a halogen substituent has been introduced and tris(trialkylsilyl)phosphite, and the halogen is replaced with a phosphonic acid bis(trialkylsilyl) group or a phosphonic acid diester group. Then, a basic solution such as a solution of sodium carbonate, potassium carbonate, or ammonia is applied to the compound after the reaction to cause deprotection.
[0048] Next, 3,4-ethylenedioxythiophene with methylenephosphonic acid groups introduced into the ethylenedioxy skeleton is mixed with a supporting electrolyte or an oxidizing agent to produce phosphonic acid group-introduced PEDOT by electrolytic polymerization or chemical polymerization. The phosphonic acid group-introduced PEDOT may be dissolved in a solvent after removing residual monomers and impurities by purification means such as ultrafiltration, cation exchange, and anion exchange. Ammonia and amine may be added after the phosphonic acid group-introduced PEDOT is dissolved in a solvent, and dissolution treatment may be performed using, for example, an ultrasonic homogenizer.
[0049] (Solid electrolytic capacitor) The cathode foil and anode foil of a solid electrolytic capacitor are foil bodies made of valve metal and stretched. Valve metals include aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. A surface-expanding layer is formed on one or both sides of the anode body. The surface-expanding layer is a sintered body made by sintering valve metal powder, or an etched layer made by etching a stretched foil, and is composed of voids between densely packed powder particles, or tunnel-like or spongy pits. The cathode foil may have a surface-expanding layer formed thereon like the anode body, or may be a plain foil without a surface-expanding layer.
[0050] The dielectric oxide film is formed on one or both sides of the anode foil on which the surface-expanding layer is formed. The dielectric oxide film is typically an oxide film formed on the surface layer of the anode body, and if the anode foil is made of aluminum, it is an aluminum oxide layer formed by oxidizing the surface of the surface-expanding layer. In the chemical conversion treatment for forming the dielectric oxide film, a voltage is applied to the anode body in a chemical conversion solution so as to achieve a desired withstand voltage. The chemical conversion solution is a solution that does not contain halogen ions, and is, for example, a phosphoric acid-based chemical conversion solution such as ammonium dihydrogen phosphate, a boric acid-based chemical conversion solution such as ammonium borate, or an adipic acid-based chemical conversion solution such as ammonium adipate.
[0051] The cathode foil may have a natural oxide film or a thin oxide film (about 1 to 10 V) formed by chemical conversion treatment. The natural oxide film is formed by the reaction of the cathode foil with oxygen in the air. Furthermore, the cathode foil may have a layer made of a metal nitride, a metal carbide, or a metal carbonitride formed by a vapor deposition method, or a layer containing carbon formed on the surface.
[0052] The cathode foil may be a laminate of a metal layer and a carbon layer. The cathode foil is disposed with the carbon layer facing the anode foil. The carbon layer is formed by coating a slurry or paste on the solid electrolyte layer after the solid electrolyte layer is formed on the anode body, and then curing the layer by heating. The metal layer is, for example, a silver layer, and is formed by coating a slurry or paste on the carbon layer, and then curing the layer by heating.
[0053] The solid electrolyte layer is formed by using a polymer solution. The polymer solution is immersed in the polymer solution and then dried to attach the solid electrolyte layer to various objects. The objects are anode foils, or anode foils, cathode bodies, and separators, or capacitor elements that are assemblies incorporating anode foils, cathode foils, and separators.
[0054] The capacitor element may include a second solid electrolyte layer forming step for forming a solid electrolyte layer in addition to the solid electrolyte layer formed using the polymer solution containing the phosphonic acid group-introduced PEDOT. The second solid electrolyte layer may be formed, for example, by chemical polymerization or electrolytic polymerization in which a monomer of 3,4-ethylenedioxythiophene or a derivative thereof is polymerized, or by using a dispersion liquid in which a polymer of 3,4-ethylenedioxythiophene or a derivative thereof is dispersed.
[0055] After the immersion, the solvent of the polymer solution is removed by a drying process. The temperature environment in the drying process is, for example, 40°C to 200°C, and the drying time is, for example, in the range of 3 minutes to 180 minutes. The drying process may be repeated multiple times. Drying may be performed in a reduced pressure environment, for example, by reducing the pressure to 5 kPa to 100 kPa. In addition to immersion, the polymer solution may be applied by dripping or spraying.
[0056] Examples of the separator include cellulose papers such as kraft, Manila hemp, esparto, hemp, and rayon, and mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins. These resins can be used alone or in combination.
[0057] The separator separates the anode body and the cathode body to prevent shorting between them, and also holds the solid electrolyte between the anode body and the cathode body. If the shape of the solid electrolyte can be maintained by itself and the cathode body and the anode body can be isolated by the solid electrolyte, the separator can be eliminated from the solid electrolytic capacitor.
[0058] The capacitor element may be a laminated type in which the anode foil and the cathode foil are alternately laminated with a separator sandwiched therebetween, or a wound type in which the anode foil and the cathode foil are alternately laminated with a separator sandwiched therebetween and wound. Alternatively, the capacitor element may be a flat type in which a solid electrolyte layer is formed on an individual anode foil, and then a carbon layer and a silver layer are formed on the solid electrolyte layer, or a flat type in which a carbon paste or a silver paste is applied and at the same time a copper foil is bonded as a lead terminal. In the case of the flat type, there is no cathode foil or separator, and the carbon layer and the silver layer correspond to the cathode foil of the solid electrolytic capacitor.
[0059] The solid electrolytic capacitor may include only a solid electrolyte layer, or may also include an electrolyte solution. The electrolyte solution is impregnated into the capacitor element after the solid electrolyte layer is formed. The electrolyte solution is responsible for repairing at least the dielectric oxide film.
[0060] The solvent of the electrolyte is not particularly limited, but a protonic organic polar solvent or an aprotic organic polar solvent can be used. As the protonic polar solvent, monohydric alcohols, polyhydric alcohols, oxyalcohol compounds, water, etc. are typified, such as ethylene glycol or propylene glycol. As the aprotic polar solvent, sulfones, amides, lactones, cyclic amides, nitriles, sulfoxides, etc. are typified, such as sulfolane, γ-butyrolactone, ethylene carbonate, or propylene carbonate.
[0061] The solute contained in the electrolytic solution includes anion and cation components, and is typically an organic acid such as adipic acid or benzoic acid or its salt, an inorganic acid such as boric acid or phosphoric acid or its salt, or a complex compound of an organic acid such as borodisalicylic acid and an inorganic acid or its ion-dissociable salt, and is used alone or in combination of two or more. Examples of the salts of these organic acids, salts of inorganic acids, and at least one salt of a complex compound of an organic acid and an inorganic acid include ammonium salts, quaternary ammonium salts, quaternary amidinium salts, amine salts, sodium salts, potassium salts, etc. An acid that becomes an anion and a base that becomes a cation may be added separately to the electrolytic solution as solute components.
[0062] Furthermore, other additives can be added to the electrolyte. Examples of additives include polyethylene glycol, complex compounds of boric acid and polysaccharides (mannitol, sorbitol, etc.), complex compounds of boric acid and polyhydric alcohols, boric acid esters, nitro compounds, phosphate esters, colloidal silica, etc. These may be used alone or in combination of two or more. The nitro compounds suppress the generation of hydrogen gas in the electrolytic capacitor. Examples of nitro compounds include o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, etc.
[0063] The capacitor element is inserted into a cylindrical exterior case with a bottom. A sealing body is attached to the open end of the exterior case, and the capacitor element is sealed by crimping the open end. The sealing body is made of rubber, or includes a laminate of rubber and a hard substrate. Examples of rubber include ethylene propylene rubber and butyl rubber. An anode lead and a cathode lead are connected to the anode body and the cathode body, and the anode lead and the cathode lead are drawn out from the sealing body.
[0064] In addition to being housed in a bottomed cylindrical exterior case, the capacitor element may be sealed with a laminate film or molded with a resin. Examples of the molding resin include heat-resistant resin and insulating resin. The molding resin may be formed into a thin film by a method such as dip coating or printing. In addition, the exterior may be omitted for a flat-plate type capacitor element. EXAMPLES
[0065] The polymer solution, the solid electrolytic capacitor and the manufacturing method thereof will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0066] Example 1 The polymer solution of Example 1 was prepared as follows, and the solid electrolytic capacitor of Example 1a was prepared using the polymer solution of Example 1. First, phosphonic acid group-introduced PEDOT was added to water, and an ultrasonic stirring process was performed. After the stirring process, ammonia and dimethylamine were added to the polymer solution until the pH of the polymer solution reached 9. Ammonia (A) and dimethylamine (B) were added to the polymer solution in a mass ratio of A:B=5:5. This produced the polymer solution of Example 1, in which the concentration of phosphonic acid group-introduced PEDOT was 2 wt%.
[0067] Next, for the solid electrolytic capacitor of Example 1a, aluminum foil was prepared as an anode foil and a cathode foil. A surface expansion layer was formed on the surface of the aluminum foil for the anode, and a dielectric oxide film was formed by further performing a chemical conversion treatment. A lead wire, which is an electrode extraction means, was connected to the anode foil and the cathode foil, and the anode foil and the cathode foil were wound with a manila separator interposed therebetween to prepare a capacitor element. In forming the surface expansion layer, an alternating current was passed through the aluminum foil in a solution containing hydrochloric acid to form a spongy etching pit. The dielectric oxide film was formed by performing a chemical conversion treatment in an ammonium adipate solution on the aluminum foil on which the surface expansion layer was formed, and setting the chemical conversion voltage to 55V.
[0068] This capacitor element was subjected to a chemical repair process. In the chemical repair process, the anode foil of the capacitor element was immersed in an ammonium dihydrogen phosphate solution at 90°C for 24 minutes. While immersed in the solution, a current of 10 mA was passed through the capacitor element with an applied voltage of 58 V. After the capacitor element was removed from the ammonium dihydrogen phosphate solution, it was washed with pure water and then left to dry in a 105°C temperature environment for 30 minutes.
[0069] After drying the capacitor element, the capacitor element was immersed in the polymer solution of Example 1 while reducing the pressure inside the capacitor element. The capacitor element was then left to stand for 30 minutes in a temperature environment of 100°C to dry it. As a result, a solid electrolyte containing phosphonic acid group-introduced PEDOT was formed in the capacitor element.
[0070] The capacitor element on which the solid electrolyte was formed was 6.3 mm in diameter and 5.8 mm in height, and was inserted into a cylindrical aluminum exterior case with a bottom. A rubber seal was attached to the open end of the aluminum exterior case, and the aluminum exterior case was sealed by crimping. Then, an aging treatment was performed to produce the solid electrolytic capacitor of Example 1a.
[0071] (Examples 2 to 6) Polymer solutions of Examples 2 to 6 and solid electrolytic capacitors of Examples 2a to 5a were produced. The polymer solutions of Examples 2 to 6 were the same as Example 1 in that they contained ammonia and dimethylamine, but the pH of the polymer solutions or the mass ratio of ammonia to dimethylamine were different.
[0072] In the polymer solution of Example 2, the mass ratio is 5:5, the same as in Example 1, but the pH is 10. In the polymer solution of Example 3, the pH is 9, the same as in Example 1, but the mass ratio of ammonia (A) and dimethylamine (B) is A:B=1:9. In the polymer solution of Example 4, the pH is 10, and the mass ratio of ammonia (A) and dimethylamine (B) is A:B=1:9. In the polymer solution of Example 5, the pH is 9, the same as in Example 1, but the mass ratio of ammonia (A) and dimethylamine (B) is A:B=9:1. In the polymer solution of Example 6, the pH is 10, and the mass ratio of ammonia (A) and dimethylamine (B) is A:B=9:1.
[0073] The polymer solutions of Examples 2 to 6 were the same as the polymer solution of Example 1, except that phosphonic acid group-introduced PEDOT was dissolved therein and water was used as the solvent. The solid electrolytic capacitors of Examples 2a to 6a had the same configuration as the solid electrolytic capacitor of Example 1a, except that the solid electrolyte layer was formed from the polymer solutions of Examples 2 to 6, and were produced by the same method and under the same conditions.
[0074] (Comparative examples, etc.) A polymer solution of Comparative Example 1 and a solid electrolytic capacitor of Comparative Example 1a were prepared corresponding to the polymer solutions of Examples 1 to 6 and the solid electrolytic capacitors of Examples 1a to 6a. Only ammonia was added as an alkaline compound to the polymer solution of Comparative Example 1, and amine was excluded. Comparative Example 1 is the same as the polymer solution of Example 1 in other respects, including the fact that phosphonic acid group-introduced PEDOT was dissolved, that water was used as a solvent, and that ammonia was added until the pH of the polymer solution reached 9.
[0075] The solid electrolytic capacitor of Comparative Example 1a was produced using the polymer solution of Comparative Example 1. Except for the fact that the solid electrolyte layer was formed from the polymer solution of Comparative Example 1, the solid electrolytic capacitor of Comparative Example 1a had the same configuration as the solid electrolytic capacitor of Example 1a and was produced by the same manufacturing method and under the same conditions.
[0076] (Comparative examples, etc.) Polymer solutions of Reference Examples 1 and 2 and solid electrolytic capacitors of Reference Examples 1a and 2a were prepared. The polymer solution of Reference Example 1 differs from Comparative Example 1 in that the pH is 10. The polymer solution of Reference Example 2 differs from Comparative Example 1 in that the pH is 11. The solid electrolytic capacitors of Reference Examples 1a and 2a were prepared using the polymer solutions of Reference Examples 1 and 2. Except for the fact that the solid electrolyte layers were formed using the polymer solutions of Reference Examples 1 and 2, the solid electrolytic capacitors of Reference Examples 2a and 3a had the same configuration as the solid electrolytic capacitors of Example 1a and Comparative Example 1a, and were prepared by the same manufacturing method and under the same conditions.
[0077] The electrostatic capacitance (Cap) and equivalent series resistance (ESR) of the solid electrolytic capacitors of Examples 1a to 6a, Comparative Example 1a, and Reference Examples 1a and 2a were measured. Cap and ESR were measured at a temperature of 20°C using an LCR meter (model number ZM2376, manufactured by NF Corporation). Cap was measured at two frequencies, 120 Hz and 10 kHz, and ESR was measured at a frequency of 100 kHz. The DC bias was 1.5 V, and the AC current level was a sine wave of 1.0 Vrms.
[0078] The measurement results are shown in Table 1 below. Based on Table 1 below, the scatter diagrams of each characteristic are summarized in Figs. 1 to 3. Fig. 1 shows Cap at a measurement frequency of 120 Hz. Fig. 2 shows Cap at a measurement frequency of 10 kHz. Fig. 3 shows ESR at a measurement frequency of 100 kHz. The horizontal axis of each figure is the mass ratio A:B of the alkaline compound A to the alkaline compound B in each series. In each figure, the plots of open triangles are the series of pH 9 of Examples 1, 3 and 5, the plots of open squares are the series of pH 10 of Examples 2, 4 and 6, the plots of filled triangles are Comparative Example 1, the plots of filled squares are Reference Example 1, and the plots of filled circles are Reference Example 2.
[0079] (Table 1) TIFF2025032805000003.tif156168
[0080] The polymer solution of Comparative Example 1 contains only ammonia and has a pH of 9. The polymer solution of Comparative Example 1 gelled. That is, in Comparative Example 1, the phosphonic acid group-introduced PEDOT was not solubilized and aggregated. Therefore, as shown in Table 1 and Figures 1 to 3, the ESR of the solid electrolytic capacitor of Comparative Example 1a was very high and the capacitance was low.
[0081] The polymer solution of Reference Example 1 contains only ammonia, but has a pH of 10. When the pH is 10, the aggregation of the phosphonic acid group-introduced PEDOT is suppressed and solubilized, even with ammonia, which is weakly basic. Therefore, as shown in Table 1 and Figures 1 to 3, the solid electrolytic capacitor of Reference Example 1a has a high capacitance and a low ESR.
[0082] The polymer solution of Reference Example 2 contains only ammonia, but has a pH of 11. When the pH is 11, even with ammonia, which is weakly basic, the capacitance of the solid electrolytic capacitor of Reference Example 1a is very high, as shown in Table 1 and Figures 1 to 3. However, when the pH is 11, dedoping is promoted even in the case of the phosphonic acid group PEDOT, so the ESR of the solid electrolytic capacitor of Reference Example 2a is quite high.
[0083] On the other hand, the polymer solution of Example 1 has a pH of 9, but the aggregation of the phosphonic acid group-introduced PEDOT is suppressed and the phosphonic acid group-introduced PEDOT is solubilized. Therefore, as shown in Table 1 and Figures 1 to 3, the polymer solution of Example 1 has a higher capacitance than Comparative Example 1. The ESR of the polymer solution of Example 1 is much lower than Comparative Example 1. The polymer solution of Example 2 has a pH of 10, and has a higher capacitance and a lower ESR than Reference Example 1, which also has a pH of 10.
[0084] Moreover, the polymer solution of Example 4 has a large amount of strongly basic amine added and a pH of 10. Therefore, as shown in Table 1 and Figures 1 to 3, the solid electrolytic capacitor of Example 4a has a good capacitance, but a higher ESR than Examples 1 to 3. Moreover, the polymer solution of Example 5 has a small amount of strongly basic amine added. Therefore, the solid electrolytic capacitor of Example 5a, which has a pH of 9, has a relatively lower capacitance than the other Examples in terms of solubilization of the phosphonic acid group-introduced PEDOT.
[0085] Thus, according to Table 1 and Figures 1 to 3, it was confirmed that a polymer solution containing phosphonic acid group-introduced PEDOT, amine, and ammonia can increase the capacitance of a solid electrolytic capacitor and reduce the ESR of the solid electrolytic capacitor. It was also confirmed that the ESR of a solid electrolytic capacitor can be particularly reduced when the pH is less than 10. It was also confirmed that the capacitance of a solid electrolytic capacitor can be particularly increased by increasing the amount of amine added, for example, to a mass ratio of ammonia (A) to amine (B) greater than A:B=9:1. Therefore, by setting the pH at 10 and adding an amine in a mass ratio equal to or greater than the amount of ammonia added, it is possible to achieve a particularly high compatibility between the capacitance and the ESR.
[0086] (Examples 7 to 14) Polymer solutions of Examples 7 to 14 and solid electrolytic capacitors of Examples 7a to 14a were produced. The polymer solutions of Examples 7 to 14 contain ammonia and diethylamine. The polymer solution of Example 7 has a pH of 9, and the mass ratio of ammonia (A) to diethylamine (B) is A:B=5:5. The polymer solution of Example 8 has a pH of 10, and the mass ratio of ammonia (A) to diethylamine (B) is A:B=5:5.
[0087] The polymer solution of Example 9 has a pH of 9, and the mass ratio of ammonia (A) to diethylamine (B) is A:B=1:9. The polymer solution of Example 10 has a pH of 10, and the mass ratio of ammonia (A) to diethylamine (B) is A:B=1:9.
[0088] The polymer solution of Example 11 has a pH of 8, and a mass ratio of ammonia (A) to diethylamine (B) is A:B=9:1. The polymer solution of Example 12 has a pH of 9, and a mass ratio of ammonia (A) to diethylamine (B) is A:B=9:1. The polymer solution of Example 13 has a pH of 10, and a mass ratio of ammonia (A) to diethylamine (B) is A:B=9:1. The polymer solution of Example 14 has a pH of 11, and a mass ratio of ammonia (A) to diethylamine (B) is A:B=9:1.
[0089] The polymer solutions of Examples 7 to 14 were the same as the polymer solution of Example 1, except that phosphonic acid group-introduced PEDOT was dissolved therein and water was used as the solvent. The solid electrolytic capacitors of Examples 7a to 14a had the same configuration as the solid electrolytic capacitor of Example 1a, except that the solid electrolyte layer was formed from the polymer solutions of Examples 7 to 14, and were produced by the same method and under the same conditions.
[0090] (Characteristics test) The capacitance (Cap) and equivalent series resistance (ESR) of the solid electrolytic capacitors of Examples 7a to 14a were measured. The method and conditions for measuring Cap and ESR were the same as those of Examples 1 and 1a.
[0091] The measurement results are shown in Table 2 below. Based on Table 2 below, the scatter diagrams of each characteristic are summarized in Figures 4 to 6. Figure 4 shows the Cap at a measurement frequency of 120 Hz. Figure 5 shows the Cap at a measurement frequency of 10 kHz. Figure 6 shows the ESR at a measurement frequency of 100 kHz. The horizontal axis of each figure is the mass ratio A:B of the alkaline compound A to the alkaline compound B in each series. In each figure, the plots of open triangles are the pH 9 series of Examples 7, 9 and 12, the plots of open squares are the pH 10 series of Examples 8, 10 and 13, the plots of open circles are the pH 8 series of Example 11, and the plots of open diamonds are the pH 11 series of Example 14.
[0092] (Table 2) TIFF2025032805000004.tif141168
[0093] As shown in Table 2, the solid electrolytic capacitors of Examples 7a to 9a have high capacitance and low ESR. This confirms that the polymer solution containing phosphonic acid group-introduced PEDOT, ammonia, and amine can increase the capacitance of the solid electrolytic capacitor while keeping the ESR of the solid electrolytic capacitor low, regardless of the type of amine. In particular, the solid electrolytic capacitor of Example 9a has a higher capacitance while keeping the ESR low compared to the solid electrolytic capacitor of Example 10a. Therefore, it is confirmed that the pH of the polymer solution is preferably less than 10.
[0094] The polymer solutions of Examples 11 to 14 have a mass ratio of ammonia (A) to diethylamine (B) of 9:1. In this way, when the amount of ammonia, which is weakly basic, is relatively greater than that of amine, it was confirmed that the pH is preferably set to 10 in consideration of the balance between aggregation, particle size reduction, and dedoping of the phosphonic acid group-introduced PEDOT. However, it is more preferable to add the amine in a mass ratio equal to or greater than the amount of ammonia.
[0095] (Examples 15 to 17) Polymer solutions of Examples 15 to 17 and solid electrolytic capacitors of Examples 15a to 17a were prepared. The polymer solutions of Examples 15 to 17 differ in the type of amine contained together with ammonia. Trimethylamine was added to the polymer solution of Example 15. Ethyldimethylamine was added to the polymer solution of Example 16. Dimethylaminoethanol was added to the polymer solution of Example 17.
[0096] The polymer solutions of Examples 15 to 17 are common in that they contain dissolved PEDOT with a phosphonic acid group introduced therein, have a pH of 10, have a mass ratio of ammonia (A) to amine (B) of A:B=9:1, and use water as a solvent, and the manufacturing method and manufacturing conditions are the same as those of the polymer solution of Example 1. The solid electrolytic capacitors of Examples 15a to 17a have the same configuration as the solid electrolytic capacitor of Example 1a, except that the solid electrolyte layer is formed from the polymer solution of Examples 15 to 17, and were manufactured by the same manufacturing method and under the same conditions.
[0097] (Characteristics test) The capacitance (Cap) and equivalent series resistance (ESR) of the solid electrolytic capacitors of Examples 15a to 17a were measured. The method and conditions for measuring Cap and ESR were the same as those of Examples 1 and 1a.
[0098] The measurement results are shown in Table 3 below. (Table 3) TIFF2025032805000005.tif66168
[0099] As shown in Table 3, even in the case of a polymer solution containing ammonia, triethylamine, ethyldimethylamine, and dimethylaminoethanol, the solid electrolytic capacitors of Examples 15a to 17a exhibit high capacitance while maintaining a low ESR. Therefore, it was confirmed that adding not only secondary amines but also amines in general together with ammonia to a polymer solution containing dissolved phosphonic acid group-introduced PEDOT can bring out good capacitance from the solid electrolytic capacitor.
Claims
1. a polymer of 3,4-ethylenedioxythiophene having a methylenephosphonic acid group introduced into an ethylenedioxy skeleton; amines and ammonia, containing, A conductive polymer solution for capacitors, characterized by:
2. the amine being a secondary amine or a tertiary amine; 2. The conductive polymer solution for a capacitor according to claim 1,
3. a pH of less than 10; 3. The conductive polymer solution for a capacitor according to claim 2,
4. pH is 9 or more; 4. The conductive polymer solution for a capacitor according to claim 3,
5. The pH is about 9.
4. The conductive polymer solution for a capacitor according to claim 3,
6. the amine is contained in the mixture in a mass ratio equal to or greater than the ammonia content; 2. The conductive polymer solution for a capacitor according to claim 1,
7. an anode foil having a dielectric oxide film formed thereon; A solid electrolyte layer including a conductive polymer; Equipped with The conductive polymer is a polymer of 3,4-ethylenedioxythiophene having a methylenephosphonic acid group introduced into an ethylenedioxy skeleton, the solid electrolyte layer contains an amine and ammonia; A solid electrolytic capacitor characterized by:
8. A method for manufacturing a solid electrolytic capacitor having an anode foil on which a dielectric oxide film is formed, comprising the steps of: a step of forming a solid electrolyte layer by applying the conductive polymer solution for a capacitor according to claim 1 to an anode foil and drying the applied conductive polymer solution; A method for producing a solid electrolytic capacitor comprising the steps of:
Citation Information
Patent Citations
Capacitor and its method for manufacturing
JP2006287182A
Capacitor and method of manufacturing the same
JP2014067949A
Electrolytic capacitor and method for manufacturing same
WO2018123255A1